Hospitals With the Highest Intensive Care Utilization Provide Lower Quality Pneumonia Care to the Elderly*. Issue 6 (June 2015) - Sjoding, Michael W.; Prescott, Hallie C.; Wunsch, Hannah; Iwashyna, Theodore J.; Cooke, Colin R.
Abstract : Objective: Quality of care for patients admitted with pneumonia varies across hospitals, but causes of this variation are poorly understood. Whether hospitals with high ICU utilization for patients with pneumonia provide better quality care is unknown. We sought to investigate the relationship between a hospital's ICU admission rate for elderly patients with pneumonia and the quality of care it provided to patients with pneumonia. Design: Retrospective cohort study. Setting: Two thousand eight hundred twelve U.S. hospitals. Patients: Elderly (age ≥ 65 years) fee-for-service Medicare beneficiaries with either a (1) principal diagnosis of pneumonia or (2) principal diagnosis of sepsis or respiratory failure and secondary diagnosis of pneumonia in 2008. Interventions: None. Measurements and Main Results: We grouped hospitals into quintiles based on ICU admission rates for pneumonia. We compared rates of failure to deliver pneumonia processes of care (calculated as 100 – adherence rate), 30-day mortality, hospital readmissions, and Medicare spending across hospital quintile. After controlling for other hospital characteristics, hospitals in the highest quintile more often failed to deliver pneumonia process measures, including appropriate initial antibiotics (13.0% vs 10.7%; p < 0.001), and pneumococcal vaccination (15.0% vs 13.3%; p = 0.03) compared with hospitals in quintiles 1–4. Hospitals in the highest quintile of ICU admission rate for pneumonia also had higher 30-day mortality, 30-day hospital readmission rates, and hospital spending per patient than other hospitals. Conclusions: Quality of care was lower among hospitals with the highest rates of ICU admission for elderly patients with pneumonia; such hospitals were less likely to deliver pneumonia processes of care and had worse outcomes for patients with pneumonia. High pneumonia-specific ICU admission rates for elderly patients identify a group of hospitals that may deliver inefficient and poor-quality pneumonia care and may benefit from interventions to improve care delivery. Abstract : Supplemental Digital Content is available in the text.